An item-by-item subject classification of papers published in journals covered by the SSCI database using reference analysis - Glänzel, W.; Schubert, A.; Schoepflin, U.; Czerwon, H. J. (Scientometrics, 1999)
Paper presented at the Seventh international conference of the International Society for Scientometrics and Informetrics, Colima, Mexico, 5-8 July 1999. A serious shortcoming of bibliometric studies based on the Social Sciences Citation Index is the lack of a universally applicable subject classification scheme as individual papers are concerned. Presents the results of an item-by-item subject classification approach, where assignment is based on the analysis of the subject categories of reference literature. This analysis extends the results of an earlier study on the possibility of delimiting subfields in the hard and life sciences based on reference analysis. (Original abstract - amended)